A targetable fluorescent probe for dSTORM super-resolution imaging of live cell nucleus DNA. Issue 13 (25th January 2019) - Zhang, Xiaodong; Ye, Zhiwei; Zhang, Xinfu; Man, Huizi; Huang, Zhenlong; Li, Ning; Xiao, Yi
Abstract : HoeSR, a nucleus specific probe for dSTORM super-resolution imaging of nucleus DNA in live cells, was designed by conjugating a rhodamine fluorophore and a Hoechst tag. Abstract : HoeSR, a nucleus specific probe for dSTORM super-resolution imaging of nucleus DNA in live cells, was designed by conjugating a rhodamine fluorophore and a Hoechst tag. HoeSR labels the cell nucleus in a wash-free way and emits intensive fluorescence exclusively in the nucleus. With the aid of HoeSR, nucleus nanostructures at different mitosis stages were observed through super-resolution imaging.